Electromagnetic Interference with Protocolized Electrosurgery Dispersive Electrode Positioning in Patients with Implantable Cardioverter Defibrillators. (April 2019) - Schulman, Peter M.; Treggiari, Miriam M.; Yanez, N. David; Henrikson, Charles A.; Jessel, Peter M.; Dewland, Thomas A.; Merkel, Matthias J.; Sera, Valerie; Harukuni, Izumi; Anderson, Ryan B.; Kahl, Ed; Bingham, Ann; et al.
Editor's Perspective: What We Already Know about This Topic: Electromagnetic interference from monopolar electrosurgery may disrupt implantable cardioverter defibrillators. Current management recommendations by the American Society of Anesthesiologists and Heart Rhythm Society are based on expert clinical opinion since there is a paucity of data regarding the risk of electromagnetic interference to implantable cardioverter defibrillators during surgery. What This Article Tells Us That Is New: With protocolized electrosurgery dispersive electrode positioning in patients with implantable cardioverter defibrillators, the risk of clinically meaningful electromagnetic interference was 7% in above-the-umbilicus noncardiac surgery and 0% in below-the-umbilicus surgery. In cardiac surgery, clinically meaningful electromagnetic interference with use of an underbody dispersive electrode was 29%. Despite protocolized dispersive electrode positioning, the risk of electromagnetic interference in above-the-umbilicus surgery is high, supporting recommendations to suspend antitachycardia therapy when monopolar electrosurgery is used above the umbilicus. With protocolized dispersive electrode positioning, the risk of electromagnetic interference in below-the-umbilicus surgery is negligible, implying that suspending antitachycardia therapy might be unnecessary in these cases. With an underbody dispersive electrode, the risk of electromagnetic interference in cardiac surgery is high. Background: The goal of this study was to determine the occurrence of intraoperative electromagnetic interference from monopolar electrosurgery in patients with an implantable cardioverter defibrillator undergoing surgery. A protocolized approach was used to position the dispersive electrode. Methods: This was a prospective cohort study including 144 patients with implantable cardioverter defibrillators undergoing surgery between May 2012 and September 2016 at an academic medical center. The primary objectives were to determine the occurrences of electromagnetic interference and clinically meaningful electromagnetic interference (interference that would have resulted in delivery of inappropriate antitachycardia therapy had the antitachycardia therapy not been programmed off) in noncardiac surgeries above the umbilicus, noncardiac surgeries at or below the umbilicus, and cardiac surgeries with the use of an underbody dispersive electrode. Results: The risks of electromagnetic interference and clinically meaningful electromagnetic interference were 14 of 70 (20%) and 5 of 70 (7%) in above-the-umbilicus surgery, 1 of 40 (2.5%) and 0 of 40 (0%) in below-the-umbilicus surgery, and 23 of 34 (68%) and 10 of 34 (29%) in cardiac surgery. Had conservative programming strategies intended to reduce the risk of inappropriate antitachycardia therapy been employed, the occurrence of clinically meaningful electromagnetic interference would have been 2 of 70 (2.9%) in above-the-umbilicus surgery and 3 of 34 (8.8%) in cardiac surgery. Conclusions: Despite protocolized dispersive electrode positioning, the risks of electromagnetic interference and clinically meaningful electromagnetic interference with surgery above the umbilicus were high, supporting published recommendations to suspend antitachycardia therapy whenever monopolar electrosurgery is used above the umbilicus. For surgery below the umbilicus, these risks were negligible, implying that suspending antitachycardia therapy is likely unnecessary in these patients. For cardiac surgery, the risks of electromagnetic interference and clinically meaningful electromagnetic interference with an underbody dispersive electrode were high. Conservative programming strategies would not have eliminated the risk of clinically meaningful electromagnetic interference in either noncardiac surgery above the umbilicus or cardiac surgery. Abstract : With protocolized electrosurgery dispersive electrode positioning in patients with implantable cardioverter defibrillators, the risk of clinically meaningful electromagnetic interference was 7% in above-the-umbilicus noncardiac surgery and 0% in below-the-umbilicus surgery. In cardiac surgery, clinically meaningful electromagnetic interference with use of an underbody dispersive electrode was 29%. Despite protocolized dispersive electrode positioning, the risk of electromagnetic interference in above-the-umbilicus surgery is high, supporting recommendations to suspend antitachycardia therapy when monopolar electrosurgery is used above the umbilicus. With protocolized dispersive electrode positioning, the risk of electromagnetic interference in below-the-umbilicus surgery is negligible, implying that suspending antitachycardia therapy might be unnecessary in these cases. With an underbody dispersive electrode the risk of electromagnetic interference in cardiac surgery is high.